2002
DOI: 10.1080/00015550252948077
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Expression of Cutaneous Lymphocyte-associated Antigen on the Peripheral Blood and Cutaneous Lymphocytes of Alopecia Areata Patients

Abstract: Alopecia areata has been reported to be accompanied by abnormal autoimmune dysfunction. We examined the expression of cutaneous lymphocyte-associated antigen (CLA), which is a skin-specific lymphocyte homing receptor, in the peripheral blood lymphocytes and skin of patients with alopecia areata. In the patients' peripheral blood, the percentage of CLA-positive CD4+ or CD8+ lymphocytes, was significantly higher than that of normal controls. The patients with severe or progressive alopecia areata showed a much h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 4 publications
2
22
0
Order By: Relevance
“…Skin-infiltrating leukocytes in AA also express cutaneous lymphocyte-associated antigen (CLA), which could be an alternative marker of activated cells for targeting and blocking skin infiltration (Ref. 159). Other activated cell-surface markers and variants expressed during migration might be additional targets.…”
Section: Leukocyte Migration and Infiltration Of Skin And Hair Folliclesmentioning
confidence: 99%
“…Skin-infiltrating leukocytes in AA also express cutaneous lymphocyte-associated antigen (CLA), which could be an alternative marker of activated cells for targeting and blocking skin infiltration (Ref. 159). Other activated cell-surface markers and variants expressed during migration might be additional targets.…”
Section: Leukocyte Migration and Infiltration Of Skin And Hair Folliclesmentioning
confidence: 99%
“…Theoretically, skin resident T cells may play initial roles in AA progression. Infiltrating T cells in AA lesions strongly express CLA, CCR4, and CCR6, suggesting skin resident T cells may be active in AA pathogenesis [21,145].…”
Section: Potential Role Of Skin Resident T Cells In Alopecia Areatamentioning
confidence: 99%
“…Based on the findings that for UVB the most effective wavelength in clearing psoriasis is at 313 nm (7–9), an experimental fluorescent lamp emitting narrow-band UVB radiation with a peak of 311 ± 2 nm was developed and explored [10]. Several clinical trials confirmed the efficacy of 311 nm narrow-band UVB in phototherapy of psoriasis [11, 12, 13, 14]. Initially, the low intensity of the tubes (40 W) resulted in longer exposure times, rendering the treatment more time consuming and expensive.…”
Section: Introductionmentioning
confidence: 99%